2021
DOI: 10.3389/fgene.2021.663617
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Data Analyses Construct a Six Immune-Related Genes Prognostic Model for Cervical Cancer in Tumor Microenvironment

Abstract: The cross-talk between tumor cells and the tumor microenvironment (TME) is an important factor in determining the tumorigenesis and progression of cervical cancer (CC). However, clarifying the potential mechanisms which trigger the above biological processes remains a challenge. The present study focused on immune-relevant differences at the transcriptome and somatic mutation levels through an integrative multi-omics analysis based on The Cancer Genome Atlas database. The objective of the study was to recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…This unexpected result also suggested that low-risk patients possessed both immune activation and immunosuppression characteristics. This interesting phenomenon was previously reported by other authors 32,33 . We think this seemingly contradictory result also illustrates the complexity of tumor immunity in young CC patients, the potential mechanism is worth exploring further.…”
Section: Discussionsupporting
confidence: 86%
“…This unexpected result also suggested that low-risk patients possessed both immune activation and immunosuppression characteristics. This interesting phenomenon was previously reported by other authors 32,33 . We think this seemingly contradictory result also illustrates the complexity of tumor immunity in young CC patients, the potential mechanism is worth exploring further.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies have shown that CD3D is involved in regulating the tumor immune microenvironment in cervical cancer, liver cancer, breast cancer and other tumors ( 12 14 ). Therefore, we further detected the expression of CD3, CD4, CD8 and PD-L1 in the tumor tissues of the included gastric cancer patients and evaluated their relationship with CD3D to explore the regulatory role of CD3D in the immune microenvironment of gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…FAM133A is a type of Cancer-Testis Antigen (CTA), a class of proteins that is highly expressed in immune privilege sites such as the brain and testis ( 57 ). High expression of FAM133A in cervical cancer and pancreatic cancer has been reported to be associated with the malignant degree of tumors ( 58 , 59 ). While in glioma, FAM133A is the downstream target of miR-155.…”
Section: Discussionmentioning
confidence: 99%